Backup Design Optimization for Water Distribution Networks - Richárd Wéber; Temirlan Tuyakbayev; Gopinathan R. Abhijith; Elad Salomons; Csaba Hős; Avi Ostfeld (Engineering Proceedings)
Rapidly growing cities need significant extensions to their water distribution networks to fulfil the water demands of the population. The design of such systems is still challenging to optimise between the robustness/reliability/vulnerability and the cost. This study presents an idea: If the network layout is already determined, how can optimal diameters be found that balance cost and service quality? On the one hand, the purpose is to determine the cheapest possible network that can still serve every consumer. On the other hand, we extend the idea by optimising all backups of the network.